Pengaruh Likuiditas Dan Investment Opportunity Set (IOS) Terhadap Leverage Pada Perusahaan Manufaktur Yang Terdaftar Di BEI - Ela Oktavia (JURNAL PUNDI, 2021)
Fast traslate Icon translate     Fast traslate Icon translate In facing competition in the current era of globalization, the most important aspect in a company is funding because in principle the company needs funds to develop its business. The source of these funds can come from internal and external companies. The purpose of this study is to discover the effect of liquidity and investment opportunity on leverage both simultaneously and in part. The object used is all manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2018, the sampling technique uses purposive sampling technique and 47 companies are obtained as samples. The data analysis method used in this paper is regression analysis in panel data and uses E-views 8 in processing the data. The results showed that liquidity had a negative and significant effect on leverage while the investment opportunity set showed no significant effect on leverage.